Investigating the Relationship between ERP-Related Technostress and Employee Performance - Khanzada, Muhammad Mustafeez ur Rehman; Khan, Shaheryar; Alam, Fawad; Nagi, Sadaf; Kamal, Muhammad Bilal (Pakistan Business Review, 2024)
This study investigates the factors affecting the adoption of ERP systems in enhancing employee performance. Interestingly, it integrates the mediating role of Techno-Stressors to understand the negative effect of technology on the employee well-being which ultimately affects the performance of employees. The theoretical framework of this study is majorly based on the Technology Acceptance Model (TAM). TAM is most extensively applied model for the adoption of IT by end users. The data for this was collected from 123 participants in order to test the hypothesis while the hypothesis was checked with the SPSS Amos 23. This study firstly reconfirmed the TAM, stating that the intention to use ERP is driven by Perceived Usefulness (PU) and Perceived Ease of Use (PEoU). Furthermore, findings show a positive link between Intentions to use (IU) ERP systems with Usage of ERP. Additionally, the interesting part is that the study finds Usage of ERP positively impacts Employee performance but when the techno-stressor introduce as a mediator it will not enhance employee performance but instead causes stress to individuals in different forms. These insights underscore the importance of managing techno-stress to optimize ERP outcomes. It is concluded that ERP systems pave the way for substantial performance benefits, so organizations must consider and address the effects techno-stress to fully leverage these systems for sustainable productivity gains.
Keywords: Enterprise resource planning (ERP) system; techno-stressor; technology acceptance model (TAM); Employee Performance